The use of CaO:Eu3+ and Zn2SiO4:Mn2+ phosphors to increase the color quality and illumination intensity of WLEDs - Thanh Tung, Ha; An Nguyen Thi, Dieu; Xuan Le, Phan (Institute of Advanced Engineering and Science, 2023)
The lumen efficacy in remote phosphor structure displayed remarkable enhancements, which is notable for the development of white light-emitting diodes (WLEDs). Nevertheless, its quality of colour is deemed not as good as that of the conformal or in-cup phosphor structure. Therefore, the goal of this research is to achieve a better quality of colour and significant luminous flux value for remote phosphor configuration by using extra phosphor layers. In particular, the two-layer and three-layer structures with the implementation of green and red phosphors are proposed. Comparing these two structures can help pinpoint the best suited for the WLED production. The assessment of each structure’s effect on the WLEDs’ optical parameters was determined under various correlated temperatures of colour (5,600-8,500 K). The outcomes indicated that the three-layer structure enhanced the quality of colour with greater efficiency compared to the two-layer structure due to the increased color rendering index (CRI), color quality scale (CQS), and photoluminescence (PL), and reduced colour deviation. The scattering improvement of the three-layer structure is a key factor of these accomplishments, proven by the scattering theory of Mie. Therefore, the three-layer structure is potential for developing WLED production.